A new type of magnetic molecular imprinted material combined with β-cyclodextrin for the selective adsorption of zearalenone. Issue 48 (13th November 2020) - Fu, Han; Liu, Junping; Xu, Wu; Wang, Haixiang; Liao, Shenghua; Chen, Guitang
Abstract : In this paper, a new magnetic molecular imprinted polymer–cyclodextrin (MMIP–CD) material was prepared by connecting β-cyclodextrin (CD) on the surface of a magnetic molecular imprinted polymer (MMIP) and used for the rapid and specific adsorption of zearalenone (ZEN). Abstract : In this paper, a new magnetic molecular imprinted polymer–cyclodextrin (MMIP–CD) material was prepared by connecting β-cyclodextrin (CD) on the surface of a magnetic molecular imprinted polymer (MMIP) and used for the rapid and specific adsorption of zearalenone (ZEN). By using warfarin as the virtual template molecule, tetraethyl orthosilicate (TEOS) as the crosslinking agent, and (3-aminopropyl) triethoxysilane (APTES) as the functional monomer, a MMIP was produced by surface imprinting technology. Sulfobutyl ether-β-cyclodextrin attached to the surface of the MMIP under heating conditions produced a new specific adsorption material with exceptional adsorption capacity and excellent selectivity for ZEN. Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and TEM-mapping results showed that the prepared MMIP–CD had a uniform particle size of about 480 nm, and the molecularly imprinted layer was successfully wrapped on the surface of the nanoparticles with a thickness of about 50 nm, whereby the cyclodextrin was effectively attached to the surface of the MMIP. The adsorption mechanism of MMIP–CD was confirmed by kinetic adsorption and thermodynamic adsorption experiments, the maximum adsorption capacity was found to be about 30 mg g −1, and the adsorption equilibrium could be reached within 20 min. The value of IF ( Q MMIP–CD / Q MNIP ) is 4.642. This showed that compared with MNIP, MMIP–CD showed a greatly improved specific adsorption capacity of ZEN. Selective experiments proved that MMIP–CD effectively combined the advantages of MMIP and CD, enhancing the adsorption capacity together with reducing the disadvantages that MMIP cannot distinguish structural analogs and CD cannot identify hydrophobic compounds effectively. In actual sample testing, the limit of quantification (LOQ) and limit of detection (LOD) were 0.1 ng kg −1 and 0.3 ng kg −1, respectively. The stability and detection precision of this method were 0.98–2.76% and 1.67–3.88%, respectively. The results proved that MMIP–CD had good development potential in the field of selective adsorption of ZEN, and laid the foundation for follow-up research.